Shock Absorption Capacity of High-Performance Polymers for Dental Implant-Supported Restorations: In Vitro Study - Maria Menini; Francesca Delucchi; Francesco Bagnasco; Domenico Baldi; Luigi Canullo; Paolo Setti; Marco Migliorati; Enrico Simetti; Paolo Pesce (MDPI AG, 2024)
Background: Restorative materials might significantly affect load transmission in peri-implant bone. The aim of the present study is to evaluate the shock absorption capacity of two different polymeric materials to be used for implant-supported prostheses. Methods: A masticatory robot was used to compare the shock absorption capacity of veneered and non-veneered polyetherketoneketone (PEKK), Pekkton®ivory (Cendres+Mètaux), and the glass fiber-reinforced composite (GFRC), TRINIATM (Bicon). Five identical sample crowns for each of the three groups were tested. Forces transmitted at the simulated peri-implant bone were recorded and statistically analyzed. Results: The statistical analysis of forces transmitted at the simulated dental implant revealed significant differences between the materials tested and between these materials and zirconia, glass ceramic, composite resin, and acrylic resin. Only differences between PEKK and veneered PEKK and between PEKK and one of the previously tested composite resins were not statistically significant. PEKK samples demonstrated significantly greater shock absorption capacity compared to GFRC. Conclusions: PEKK revealed optimal shock absorption capacity. Further studies are needed to evaluate its efficacy in the case of long-span prostheses with reduced prosthetic volume.